Financial Reporting and Valuation: The Effect on Investment Decisions - Mui, Joanne Tan San (Digital Repository of Theses, 2025)
This research investigates the relationship between financial reporting and investment decisions, with a focus on how financial and non-financial disclosures influence investor behavior and share prices. The main objective is to examine the impact of key financial metrics, such as net profit and equity-to-debt ratio, on market valuation, while also considering the growing importance of non-financial information like environmental, social, and governance (ESG) factors. The study aims to provide empirical insights into how companies' financial stability and transparency affect investment behavior and share price movements. The scope of the research includes listed companies, focusing on the interaction between financial reporting quality and market efficiency. The study utilizes secondary data from financial statements and stock market performance, covering a range of firms over several years. The methodology primarily involves Ordinary Least Squares (OLS) regression models, with natural log transformations applied to address common statistical issues such as heteroscedasticity and autocorrelation. These models assess the influence of financial metrics on share prices while also accounting for intrinsic value and non-financial disclosures. The findings indicate a strong positive correlation between net profit, financial stability, and share prices, as well as a significant impact of non-financial information on investor behavior. The research demonstrates the importance of accurate and comprehensive financial reporting for driving investment decisions and enhancing market transparency. The study highlights key policy implications, suggesting that regulators and policymakers should enforce high standards of financial and non-financial reporting to improve market efficiency. Companies are encouraged to prioritize transparency in both financial metrics and ESG disclosures to attract investors and improve market valuation. The findings provide valuable insights for investors, emphasizing the need to consider a combination of financial stability and corporate sustainability when making investment decisions.